Proceedings of 2nd International Conference on Communication, Computing and Networking ICCCN 2018, NITTTR Chandigarh, India - Krishna, C. Rama; Dutta, Maitreyee; Kumar, Rakesh (Lecture Notes in Networks and Systems, 2019)
The book provides insights from the 2nd International Conference on Communication, Computing and Networking organized by the Department of Computer Science and Engineering, National Institute of Technical Teachers Training and Research, Chandigarh, India on March 29-30, 2018. The book includes contributions in which researchers, engineers, and academicians as well as industrial professionals from around the globe presented their research findings and development activities in the field of Computing Technologies, Wireless Networks, Information Security, Image Processing and Data Science. The book provides opportunities for the readers to explore the literature, identify gaps in the existing works and propose new ideas for research.